Analisis penyelesaian permasalahan dalam peradilan adat di Bali perspektif Siyasah Qadhaiyyah - Irawan, Trio Rizki (Maliki Interdisciplinary Journal, 2024)
The position of the Community in Indonesia is actually recognized by the state through the 1945 Constitution. Likewise in the Bali area. Habits that have long been carried out by a group of Balinese traditional communities also maintain the existing culture and traditions to organize these group communities. Balinese traditional community groups have their own rules which are commonly known as awiq-awiq. Even though there are rules, social tensions always arise within a group. To overcome this, a group must have its own judicial institution to provide a form of protection and justice for every community in the Balinese traditional group. Balinese customs have their own mechanisms for resolving various disputes. Seeing that Indonesia is always side by side with Muslim communities, there is little connection between the process goals and mechanisms of indigenous communities and the concept of Siyassah Qadhaiyyah which exists in the Islamic legal system. The resolution of problems from these two judicial concepts has similarities in that it always prioritizes the common interest and tries to provide justice that is as fair as possible for the people under its auspices, provides legal certainty and has a very important role in its existence in the environment of indigenous community groups in Bali.